One-Pot, Three-Component Synthesis of 1,8-Naphthyridine Derivatives from Heterocyclic Ketene Aminals, Malononitrile Dimer, and Aryl Aldehydes - Sun, Feilong; Zhu, Fengjuan; Shao, Xusheng; Li, Zhong (Synlett, 2015)
An efficient and versatile method was developed for the access of multisubstituted 1,8-naphthyridine derivatives through a one-pot, three-component protocol from heterocyclic ketene animals, malononitrile dimer, and aryl aldehydes in high yields. The 1,8-naphthyridines were formed via Knoevenagel condensation, aza–ene reaction, imine–enamine tautomerization, and intramolecular cyclization.
Keywords: one-pot; multicomponent reactions; heterocyclic ketene aminals; 1,8-naphthyridine; co-catalysts